Antimicrobial resistance pattern in Campylobacter strains isolated from both no-antibiotics-ever (NAE) and conventional broiler complexes: Genotypic and phenotypic characterization - Yagya Adhikari; Dianna V. Bourassa; Sabin Poudel; Matthew A. Bailey; Li Zhang; R. Jeff Buhr; Kenneth S. Macklin (Poultry Science, 2025)
Drug-resistant Campylobacter is a serious public health concern because of its increasing resistance to clinically important antimicrobials. To determine the antimicrobial resistance (AMR) pattern, the phenotypic and genotypic characteristics of Campylobacter isolated from two commercial integrated broiler complexes (No-Antibiotics-Ever (NAE) and Conventional) were studied. Genotypic analysis of AMR genes were identified using ResFinder while the phenotypic resistance test was performed using the broth microdilution method. Odds ratio and 95 % confidence limits were calculated for complex types and stages of broiler production (α=0.05). The AMR genes identified were bla OXA-61 (29 %), bla OXA-184 (4 %), tet (O) (13 %), tet (O/32/O) (12 %) and aph (3′)-III (7 %). The phenotypic results showed that 48 % (30/63) of isolates were resistant to at least one antibiotic while 13 % (8/63) of isolates were multi-drug resistant (MDR) (resistant ≥ 3 antibiotic classes). Among 30 resistant isolates, the highest resistance was observed for tetracycline (46 %) followed by clindamycin (16 %), azithromycin (10 %), erythromycin (8 %), florfenicol (8 %), nalidixic acid (2 %) and meropenem (2 %). In addition, 61 % (13/21) of Campylobacter jejuni (C. jejuni) and 40 % (17/42) of Campylobacter coli (C. coli) isolates showed resistance to at least one antimicrobial. There was no significant differences in detection of Campylobacter strain having antimicrobial resistance in the environments of different complexes and stages of broiler production (p > 0.05). However, all 8 MDR strains were isolated from a conventional broiler complex. The presence of antimicrobial resistant Campylobacter in the surroundings of farms and facilities poses a significant risk of these bacteria entering into the complex and could contaminate the final meat product, potentially resulting in prolonged foodborne illness in consumers.